Math in Motion: Exploring Sportsas a Context for Teaching Elementary Mathematics - Cibro D.S; Putri A.P; Hutahaean D.S.E; Natser R.A (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Mathematics lessons are often considered difficult and boring by most students in many different schools. One of the causes is monotonous, teacher-centered learning. To overcome this, there needs to be a breakthrough in learning. Students have fun, escape boredom, while conveying good lesson content. Currently, many students do not understand mathematics learning. One way to help students understand is to carry out activities that make it easy for students to understand mathematics. One of them is by carrying out sports. This research aims to look at the role of sports in helping students learn mathematics. This research was carried out using the literature review method, which examines and analyzes related articles. The results of this research are that sports such as jumping rope and other sports can make it easier for elementary school students to understand learning.